Functionalization of bioactive substrates with a F5SCH = CH moiety. (2nd January 2020) - Brel, Valery K.; Artyushin, Oleg I.; Moiseeva, Aleksandra A.; Sharova, Elena V.; Buyanovskaya, Anastasiya G.; Nelyubina, Yulia V.
ABSTRACT: A convenient approach to modify bioactive substrates such as daunorubicin, cytisine, and camphecene with a pentafluorosulfanylvinyl moiety have been suggested. F5 S-CH = CH derivatives of daunorubicin were obtained by acylation with reactive 4-nitrophenyl-4-(pentafluoro-λ 6 -sulfanyl)alkenyl carbonates, while the corresponding conjugates of anthracycline antibiotic daunorubicin, alkaloid cytisine and camphecene were synthesized using a click chemistry procedure. GRAPHICAL ABSTRACT: